Biomechanical analysis of segmental lumbar lordosis and risk of cage subsidence with different cage heights and alternative placements in transforaminal lumbar interbody fusion. Issue 9 (3rd July 2020) - Rastegar, Sajjad; Arnoux, Pierre-Jean; Wang, Xiaoyu; Aubin, Carl-Éric
Abstract: Cage subsidence in transforaminal lumbar interbody fusion (TLIF) is one of the concerns. The objective was to numerically assess the resulting segmental lumbar lordosis (SLL) and stresses at the bone-cage interface as functions of cage height (8- vs. 10-mm) and cage placement (oblique asymmetric, vs. anterior symmetric) for normal and osteoporotic bone quality. A L4-L5 detailed finite element model of TLIF was subjected to the functional loadings of 10 Nm in the physiological planes after the application of a 400 N follower-load. The SLL was increased by 0.9° (11%) and 1.0° (13%), respectively in oblique asymmetric and anterior symmetric cage placement with 8-mm height; they were 1.4° (18%) and 1.7° (21%) for the 10-mm cage. The maximum stresses at the cage-bone interface, in normal bone model, were increased up to 16% and 41% with the 10-mm cage and asymmetric oblique placement, respectively, and they increased up to 16% and 43% in osteoporotic bone model. The greater cage resulted to a higher simulated SLL. Oblique asymmetric placement and the use of a greater cage may increase the risk of cage subsidence. Due to the lower mechanical strength of osteoporotic bone, the risk of cage subsidence should be higher.